Investigating Effects of Cold Water Hand Immersion on Selective Attention in Normobaric Hypoxia - Gerhart, Hayden D. (Int J Environ Res Public Health, 2019)
This study investigated the effect of cold-water hand immersion on selective attention as measured by the Stroop Color Word Test in nomorbaric normoxia and hypoxia. Ten healthy men rested for 60 min, after which they immersed their non-dominant hand into 5 °C water for 15 min. The interference score of the Stroop Color Word Test and thermal sensation were measured at baseline in the final 5 min of resting and in the final 5 min of cold water hand immersion. The interference score was not influenced by hypoxia but was found to be significantly improved compared to resting in both conditions during cold water hand immersion. Selective attention improved during 15 min of cold-water hand immersion, with increased thermal sensations rated as “very cool” of the immersed arm. Cold-water hand immersion may be helpful in improving cognitive function in normoxia and normobaric hypoxia.